Where, When, and Who: Corporate Social Responsibility and Brand Value—A Global Panel Study. Issue 6 (July 2022) - Pope, Shawn; Kim, Jimi
According to surveys of companies, branding is one of the main objectives of their corporate social responsibility (CSR). With advantageous data from Brand Finance, we address three contextual factors that may condition the relationship between CSR and brand value. First, we hypothesize that the relationship between CSR and brand value obtains across major world regions and industrial sectors ("the convergence thesis"). Second, we hypothesize that the relationship has weakened with time, as companies have had increasing difficulty using CSR to differentiate their brands in a sea of CSR-espousing competitors ("the crowding out thesis"). Third, we hypothesize that the relationship between CSR and brand value is weaker where a brand's identity is different from that of its corporate owner, which may make it difficult for observers to readily link (corporate-level) CSR with its potential (lower level) brand beneficiaries ("the identity-match thesis"). We support these hypotheses with random-effects, fixed-effects, and instrumental-variable regressions before ending with contributions, limitations, implications, and potential next steps.